Understanding community antibiotic use and antimicrobial resistance in Sub-Saharan Africa: A grassroots perspective from Enugu, Nigeria - Winifred Maduko; Emmanuel Olamijuwon; Mike Kesby; Jo Mhairi Hale (PLoS ONE, 2026)
Antimicrobial resistance (AMR) is a growing global health crisis, especially in low-and middle-income countries where antibiotic access is insufficiently regulated and health systems are under-resourced. In Sub-Saharan Africa, the community is often the primary site of antibiotics decision-making, shaped by informal markets, structural barriers, and cultural norms. This study investigates antimicrobial use behaviours, perceptions of AMR, and motivations for inappropriate antibiotics use and what might motivate future change, among diverse communities in Nigeria. Using a mixed-methods design, data were collected from a baseline survey (n = 1,281), 20 interviews, and 4 focus group discussions (n = 24). Antibiotic use was widespread, with 57.7% of respondents reporting use within six months, often without prescriptions and for conditions like malaria (32.3%), cough (7.6%), and fever (4.5%), many of which are non-bacterial in origin. Of those who reported antibiotic use, 48% self-medicated, sourcing antibiotics primarily from chemist shops. Misconceptions were common; only 15.7% had heard of AMR, and many confuse it with fake drugs or allergic reactions. Novel trends such as the use of antibiotics for pregnancy termination and preventive “cleansing” emerged. Structural challenges such as poverty, poor healthcare access, and lack of regulation reinforced these behaviours. Qualitative findings highlighted a deep trust in antibiotics as a “cure-all”, low health literacy, and the central role of informal drug vendors in care delivery. Participants also offered culturally embedded recommendations, including using radio jingles, community education through religious leaders, and stronger enforcement of drug regulation. This study argues that antibiotic misuse in Nigerian communities is not solely a function of ignorance but a rational response to systemic healthcare limitations, cultural logics, and informal care networks. Tackling AMR in this context requires inclusive, community-informed interventions that address both behavioural and structural determinants of misuse. The study offers actionable insights for AMR policy, communication strategies, and community engagement in Sub-Saharan Africa.